MONITORING NITROGEN NUTRITION IN COTTON - Rosolem, Ciro Antonio [UNESP]; van Mellis, Vanessa (Sociedade Brasileira de Ciência do Solo, 2010)
Both N excess and deficiency may affect cotton yield and quality. It would therefore be useful to base the N management fertilization on the monitoring of the nutritional status. This study investigated the correlations among the following determination methods of the N nutritional status of cotton (Gossypium hirsutum L., var. Latifolia): chlorophyll readings (SPAD-502 (R), Minolta), specific-ion nitrate meter (Nitrate Meter C-141, Horiba-Cardy (R)), and laboratory analysis (conventional foliar diagnosis). Samples were taken weekly from two weeks before flowering to the fifth week after the first flower. The experiment was conducted on the Fazenda Santa Tereza, Itapeva, State of São Paulo, Brazil. The crop was fertilized with 40 kg ha(-1) N at planting and 0, 30, 60, 90, and 120 kg ha(-1) of side-dressed N. The range of leaf N contents reported as adequate for samples taken 80-90 days after plant emergence (traditional foliar diagnosis) may be used as reference from the beginning of flowering when the plant is not stressed. Specific-ion nitrate meter readings can be used as a nutritional indicator of cotton nutrition from one week after pinhead until the third week of flowering. In this case, plants are well-nourished when readings exceed 8,000 mg L(-1) NO(3)(-). The chlorophyll meter can also be used to estimate the nutritional status of cotton from the third week of flowering. In this case the readings should be above 48 in well-nourished plants.
Keywords: fertilizer; Gossypium hirsutum; foliar diagnosis; nutritional status